Proposal of a clinical care pathway for quality and safe management of headache patients: a consensus study report. Issue 10 (30th October 2020) - Pascual, Julio; Pozo-Rosich, Patricia; Carrillo, Irene; Rodríguez-Justo, Sandra; Jiménez-Hernández, Dolores; Layos-Romero, Almudena; Bailón-Santamaría, Cristina; Torres, Antonio; Martínez-García, Alba; Ignacio, Emilio; Mira, José Joaquín
Abstract : Background: Headache is one of the most prevalent and disabling conditions. Its optimal management requires a coordinated and comprehensive response by health systems, but there is still a wide variability that compromises the quality and safety of the care process. Purpose: To establish the basis for designing a care pathway for headache patients through identifying key subpathways in the care process and setting out quality and clinical safety standards that contribute to providing comprehensive, adequate and safe healthcare. Method: A qualitative research study based on the consensus conference technique. Eleven professionals from the Spanish National Health System participated, seven of them with clinical experience in headache and four specialists in healthcare management and quality. First, identification of the key subpathways in the care process for headache, barriers/limitations for optimal quality of care, and quality and safety standards applied in each subpathway. Second, two consecutive consensus rounds were carried out to assess the content of the subpathway level descriptors, until the expert agreement was reached. Third, findings were assessed by 17 external healthcare professionals to determine their understanding, adequacy and usefulness. Results: Seven key subpathways were identified: (1) primary care, (2) emergency department, (3) neurology department, (4) specialised headache unit, (5) hospitalisation, (6) outpatients and (7) governance and management. Sixty-seventh barriers were identified, the most frequent being related to diagnostic errors (36, 1%), resource deficiency (25%), treatment errors (19, 4%), lack of health literacy (13, 9%) and inadequate communications with care transitions (5, 6%). Fifty-nine quality and 31 safety standards were defined. They were related to evaluation (23.3%), patient safety (21.1%), comprehensive care (12.2%), treatment (12.2%), clinical practice guidelines (7.8%), counselling (6.7%), training (4.4%) and patient satisfaction (3.3%). Conclusions: This proposal incorporates a set of indicators and standards, which can be used to define a pathway for headache patients and determine the levels of quality.